Association of GST Genes Polymorphisms with Asthma in Tunisian Children - Chelbi Hanene; Lachheb Jihene; Ammar Jamel; Hamzaoui Kamel; Hamzaoui Agnès (Hindawi Limited, 2007)
Background. A positive association between genetic polymorphism and asthma may not be extrapolated from one ethnic group to another based on intra- and interethnic allelic and genotype frequencies differences. Objective. We assessed whether polymorphisms of GST genes (GSTM1, GSTT1, and GSTP1) are associated with asthma and atopy among Tunisian children. Methods. 112 unrelated healthy individuals and 105 asthmatic (73 atopic and 32 nonatopic) children were studied. Genotyping the polymorphisms in the GSTT1 and GSTM1 genes was performed using the multiplex PCR. The GSTP1 ILe105Val polymorphism was determined using PCR-RFLP. Results. GSTM1 null genotype was significantly associated with the increased risk of asthma (P=.002). Asthmatic children had a higher prevalence of the GSTP1Ile105 allele than the control group (43.8% and 33.5%, respectively; P=.002). Also, the presence of the GSTP1 homozygote Val/Val was less common in subjects with asthma than in control group. We have found that GSTT1 null genotype (GSTT10∗/0∗) was significantly associated with atopy (P=.008). Conclusion. Polymorphisms within genes of the GST superfamily were associated with risk of asthma and atopy in Tunisia.